What do states do with fiscal windfalls? Evidence from the pandemic - Jeffrey Clemens; Oliver Giesecke; Joshua Rauh; Stan Veuger (American Enterprise Institute (AEI), 2024)
Using variation in federal pandemic-era fiscal aid to states driven by the strength of political representation, we find that incremental pandemic-era fiscal aid to states was most likely to end up in the categories of general administrative service spending and employee pension benefit funding. Spending on categories that motivated the aid in the first place, such as healthcare, education, and infrastructure, may also have responded but does not show robust patterns. Total state government revenues and expenditures had increased by around 70 cents per incremental windfall dollar of committed federal funds by 2022. Of this, the statistically significant categorical spending effects are 38 cents to general government expenditures (the residual that in principle excludes healthcare, education, infrastructure, and other functional categories) and 7 cents to pension funding, even though the latter use was inconsistent with the objectives of the legislation. The pension contribution increases are driven by the states where public employees have above-median representation on state pension fund boards, where over 14 cents of each marginal dollar went to pension funding.
Keywords: H55; H75; J26; J45; 330; Pandemic fiscal aid; COVID-19; state and local governments; fiscal fundamentals; debt burden; pension funding; debt structure